Η πρώτη έντυπη Ελληνική μετάφραση από την Τουρκική λογοτεχνία (1800) - Κεχαγιόγλου, Γιώργος (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1997)
According to an unpublished document written in Latin and signed by the appointed Censor Regius of the Venitian censorship Ioannis Litinos (Archivio di Stato di Venezia, Riformatori dello studio di Padova, f. 333, no 592, September 13, 1800), a positive answer was given to the request of an anonymous Greek publisher in Venice (perhaps the Theodosiou publishing house) to print a Modern Greek translation of the Ottoman Turkish book Eventus Rhephae et Michrae, along with the Modern Greek translation of Marmontel’s pastorale La Bergère des Alpes. Unfortunately, we have no further information regarding these two editions of 1800 (or 1801). A thorough investigation of the Greek literary environment of the time leads the author to the supposition that Eventus Rhephae et Michrae should be a prose romance, or even a prose narrative interwoven with lyric verses (songs), most probably of the kind of hikâya/hikâye such as the short-story collections A School of Sensitive Lovers by Rigas Velestinlis (Ferraios), 1790, and Results ot Love by John Karatzas, 1792; the vivid interest in Ottoman poetry and prose during the 18th c. is well witnessed. The Ottoman model (Events regarding Refii/Retai/Refia/Rifai and Mihril) was most probably a love story, or a collection of stories and anecdotes; although an eventual identification of the genitive Rhephae with either the mystic poet of the 14th-early 15th c. Refi‘i/Rifa‘i or the anacreontic poet of the 16th c. Rewanr/ Revani and others creates a lot of problems, one could possibly recognize behind the genitive Michrae the famous lyric poetess of the beginning of the 16th c. Mihri KhatOn/Hatun or Mihn Hamm. Anyway, the unrepertoried Greek edition of Venice must be the first Greek printed translation of any Turkish literary text, and maybe the earliest printed translation worldwide of material concerning Mihr'i Khätün.